R - 6m = n.....add 6m to both sides
r = n + 6m <==
Answer:
Step-by-step explanation:
<u>Simplify the numerator:</u>
- (2x - y)/(2x + y) + (2x + y)/(3y - 6x) + 8xy/(12x² - 3y²) =
- (2x - y)/(2x + y) - (2x + y)/3(2x - y) + 8xy/3(2x + y)(2x - y) =
- [3(2x - y)² - (2x + y)² + 8xy] / [3(2x + y)(2x - y)] =
- [12x² - 12xy + 3y² - 4x² - 4xy - y² + 8xy] / [3(2x + y)(2x - y)] =
- [8x² - 8xy + 2y²] / [3(2x + y)(2x - y)] =
- 2{2x - y)² / [3(2x + y)(2x - y)] =
- 2(2x - y) / [3(2x + y)]
<u>Simplify the denominator:</u>
- (4x²y - 2xy²) / (6x + 3y) =
- 2xy(2x - y) / [3(2x + y)]
<u>Now simplify the remainder of the expression:</u>
- 2(2x - y) / [3(2x + y)] × [3(2x + y)]/[2xy(2x - y}] =
- 1/xy
Answer:
The answer is B. Two Foci, hope this helps! :)
Answer:
31.25
Step-by-step explanation:
25/12=2.083333
15 x 2.0833333=31.24999999995
round up to get 31.25